Branding dan Redesain Logo dan Kemasan : BUMDes Desa Bola, dan BUMDes Desa Watu Krus - Hekopung, Yesita Madona Vikmart Mada Hekopung; Adur, Valentin Romualda Gaudiosa Bella; Ermolis, Agustinus; Danil, Charlos (Dinasti Research, 2026)
MSMEs play a vital role in supporting the local economy in Bola District, Sikka Regency, East Nusa Tenggara Province. However, preliminary interviews with the BUMDES of Bola Village and Watu Krus Village indicated challenges related to a lack of understanding of branding, weak marketing strategies, and a lack of creative innovation in product introductions. A simple visual identity makes MSME products less competitive in the market. In response to these challenges, the Visual Communication Design Study Program and the Entrepreneurship Study Program implemented a Community Service (PkM) program to provide branding assistance and design a more professional visual identity. The program ran from June to November, encompassing field surveys, partner coordination, needs analysis, mentoring per BUMDES, and design finalization. This program aims to increase the competitiveness of local products and strengthen the independence of the village's creative economy through collaboration between academics, government, and the community.